(untitled) (Patan Pragya, 2020)
Rai is an indigenous people and decedent of Kirati dynasty, inhabitant of eastern part of Nepal. It is known as Kirat Pradesh before the unification of Nepal. Now, Kirat Pradesh is became political word in Nepal for name of province number 1 but not endorse till present. The Chamling Rai society is comprised different interdependent parts and units as like religion, culture, economy, polity, educational etc. Kirat religion is a part of Rai community constituted by the different units and interdepended among different parts. The Chamling word Nachhung (shaman) is called priest of the Kirat religion. So, this article focuses on the Nachhung who is the Rai priest, shaman and healer as functional unit of theRai society. The main research questions if how the Nachhung plays function as the being part of Rai society and contribute to existence of Rai society as whole. It explores the interdependence of Nachhung on other parts like rite and ritual, marriage, feast and festival, community, health, social and religious activities.